Functioning of colour terms in Ukrainian and English literary texts : similes and synaesthesia - Lukianets, Halyna (My University, 2019)
The article deals with the cross-cultural usage of Ukrainian and English colour terms in literary texts not only as means of colour nomination, but also as ways to represent authors’ perception of colours. When colour terms function as stylistic devises, such as similes and synaesthesia, they express authors’ emotions and have influence on readership due to semantic shifts of lexical units.
Keywords: colour terms; cross-cultural studies; literary texts; similes; synaesthesia; колороніми; міжкультурні дослідження; літературні тексти; порівняння; синестезія; кафедра іноземних мов професійного спрямування